Antibacterial Activity of Shwetavarshabuvadi Formulation Extracts on Various Pathogens Causing Skin and Soft Tissue Infections – An In Vitro Study - Ahlawat, Manita; Godatwar, Pawan Kumar (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: The present study was carried out with an objective to investigate the antimicrobial potentials of various extracts of Shwetavarshabuvadi formulation on common pathogens causing skin and soft tissue infections. Methods: Aqueous and ethanolic extracts of study formulation with three concentrations 10%, 20%, 30% were prepared using Continuous extraction method by Soxhlet Apparatus. All extracts were tested against Staphylococcus aureus (ATCC 29213), Escherichia coli (ATCC 25922), and Pseudomonas aeruginosa (ATCC 27853). The susceptibility tests were performed using Agar ditch method. The antibacterial activity was assessed on the basis of Zone of inhibition and activity index. Results :As compared with standard drug (doxycycline), the results revealed that all extracts possesses anti-bacterial activity in dose dependent manner but aqueous extract was found to have maximum activity against all pathogens taken in this study. Maximum antibacterial activity was reported against S.aureus followed by P.aeruginosa by all extracts. E.Coli was resistant at 10 % conc. of both extracts of the study formulation. Conclusion: In vitro findings of this study confirmed antibacterial activity of Shwetavarshabuvadi formulation on common pathogens causing skin and soft tissue infections.